PHENOMENOLOGICAL APPROACH IN ISLAMIC STUDIES: PARADIGMS, FACTORS, AND IMPLICATIONS - Ahmad Fawaid Hariry; Zulfi Mubaraq; Muh. Khairul Wajedi Imami; Muh. Khalifa Mujaddid Satria Wibawa; T. M. Hadie Subulana (Manarul Qur'an: Jurnal Ilmiah Studi Islam, 2026)
A deeper study on the Phenomenological Approach is very important, considering that this approach continues to be the subject of discussion and development of scientific studies. The purpose of this paper is to understand three main aspects: paradigm, factors, and their implications for religious life. The research method uses a qualitative method through literature studies with a descriptive phenomenological approach. Data collection was carried out through documentation of a number of related literature, which were analyzed descriptively. The results of the study show three main findings. First, in terms of paradigm, the phenomenological approach in Islamic studies is manifested in three forms: (1) symptoms (phenomena), (2) history, and (3) reality. Second, factors that influence this approach are divided into internal and external. Internal factors include: (1) theological understanding, (2) religious tradition, and (3) subjective perspective. External factors include: (1) life experience, (2) social environment, and (3) community culture. Third, this approach has positive implications for community life, namely: (1) deepening religious experience, (2) understanding the cultural context, and (3) strengthening the value of tolerance. On the other hand, there are negative implications namely: (1) limited objectivity, (2) difficulties in generalizing findings, and (3) methodological constraints. Thus, the phenomenological approach contributes significantly to understanding the complexity of religion, both at the individual and group levels of Muslim society. Despite its limitations, this approach remains relevant for development to enrich more contextual and reflective Islamic studies.